ANALISIS PERMINTAAN KARTU KREDIT DI BNI CARD CENTER MEDAN - Wulan Rahmadiana (Ekonomi dan Keuangan, 2013)
ABSTRACTThis research has purposes to know how the credit card growth and to know the credit card demand factors of credit card distribution into BNI Card Center Medan costumers. The analysis of method used in this research is descriptive method, where the obtained data will be analyzed by tabulation until getting amount and percentage from researched variable as result. So in the result, there are many informations will describe the growth and factors which influence credit card demand at BNI Card Center Medan.Tabulation result of some question shows that free tuition in the first year become an indicator that have the highest answar, where it is the main factor that influenced the credit card demand at BNI Card Center Medan. The percentage is about 48,96 percent equivalent as 53 authors. The second factor is about life style, the percentage 46,86 percent equivalent as 45 authors. ”Buy now, pay later” principle is the other factor that influenced. The percentage is about 45,83 percent equivalent as 44 authors who answer the questions.Keyword : Demand, Credit Card, BNI Card Center Medan